Effective team-based primary care: observations from innovative practices - Wagner, Edward H. (BMC Fam Pract, 2017)
BACKGROUND: Team-based care is now recognized as an essential feature of high quality primary care, but there is limited empiric evidence to guide practice transformation. The purpose of this paper is to describe advances in the configuration and deployment of practice teams based on in-depth study of 30 primary care practices viewed as innovators in team-based care. METHODS: As part of LEAP, a national program of the Robert Wood Johnson Foundation, primary care experts nominated 227 innovative primary care practices. We selected 30 practices for intensive study through review of practice descriptive and performance data. Each practice hosted a 3-day site visit between August, 2012 and September, 2013, where specific advances in team configuration and roles were noted. Advances were identified by site visitors and confirmed at a meeting involving representatives from each of the 30 practices. RESULTS: LEAP practices have expanded the roles of existing staff and added new personnel to provide the person power and skills needed to perform the tasks and functions expected of a patient-centered medical home (PCMH). LEAP practice teams generally include a rich array of staff, especially registered nurses (RNs), behavioral health specialists, and lay health workers. Most LEAP practices organize their staff into core teams, which are built around partnerships between providers and specific Medical Assistants (MAs), and often include registered nurses (RNs) and others such as health coaches or receptionists. MAs, RNs, and other staff are heavily involved in the planning and delivery of preventive and chronic illness care. The care of more complex patients is supported by behavioral health specialists, RN care managers, and pharmacists. Standing orders and protocols enable staff to act independently. CONCLUSIONS: The 30 LEAP practices engage health professional and lay staff in patient care to the maximum extent, which enables the practices to meet the expectations of a PCMH and helps free up providers to focus on tasks that only they can perform. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12875-017-0590-8) contains supplementary material, which is available to authorized users.